Role of Imaging in the Diagnosis and Management of Complete Androgen Insensitivity Syndrome in Adults. (23rd May 2013) - Nezzo, Marco; De Visschere, Pieter; T'Sjoen, Guy; Weyers, Steven; Villeirs, Geert
Abstract : Complete androgen insensitivity syndrome is an X-linked recessive androgen receptor disorder characterized by a female phenotype with an XY karyotype. Individuals affected by this syndrome have normal female external genitalia but agenesis of the Müllerian duct derivatives, that is, absence of the Fallopian tubes, uterus, cervix, and the proximal part of the vagina, with presence of endoabdominal, labial, or inguinal testes. The estimated prevalence is between 1 and 5 in 100, 000 genetic males. Complete androgen insensitivity syndrome can be diagnosed as a result of mismatch between the prenatal sex prediction and the phenotype at birth, can be detected by chance, or remain undetected until investigations for primary amenorrhea. Imaging can be important both to diagnose the pathology and to localize gonads prior to surgical treatment. In this paper, we present three cases of complete androgen insensitivity syndrome in adult women of 34, 22, and 38 years old.